Kajian Regulasi Covid-19 Pada Pola Sebaran Covid-19 di Kabupaten Luwu Timur - Lukman, Eva Nurrahmi; Tambunan, Mangapul Parlindungan; Tambunan, Rudy Parluhutan (LaGeografia, 2021)
Covid-19 is a health catastrophe that is currently insurmountable. All over the world, even in Indonesia, this epidemic is getting worse. Various efforts and regulations have been made by the government, but positive cases are increasing. The purpose of this study is to describe the distribution, analyze the movement of Covid and evaluate the factors causing the spread of Covid-19 in East Luwu Regency. The research method is descriptive analysis method. The data collection technique used is by conducting interviews and literature studies by collecting data from books, news media, and previous research journals, and using GIS (Geography Information System with spatial overlay technique to produce a map of the distribution of covid-19. shows that on November 22, 2020 there were 1,648 cases of Covid-19 infection in East Luwu Regency. This has led to several local government regulations in preventing the spread of Covid-19. This discussion focuses on three factors: empathy, positive mood, and social attitude. Comments The event ended with a series of brief suggestions addressed to local governments and stakeholders involved in encouraging public compliance with regulations to prevent the spread of the Covid-19 virus through mass media communication.